(untitled) (Journal of Informatics Education and Research, 2023)
Training plays a crucial role in nurturing talent and converting any enterprise into ‘a learning organization. Both technology and talent can outperform if they are used strategically. A firm can gain an advantage in the marketplace by increasing its efficiency and effectiveness with the aid of information technology (IT). No country’s economy has not significantly expanded as a result of the efforts of its small and medium-sized firms. Training creates a link between representatives’ current roles and the requirements of their future jobs in a methodical way that increases efficiency. “Employees training have been a matter of concern in IT sectors because of the fast changing technology and environment.”All industries are experiencing a fairly high pace of technical progress, and every other day we see new products, pieces of machinery, or pieces of equipment with more advanced capabilities that consumers need to be aware of. The present article aims to analyze the impact of training on IT employees in Gujrat state. Structured questionnaire was administered for 70 IT employees. The study is significant as it deals with knowledge transfer, principles, and behaviors required for someone to perform their profession.